Stomach cancer mortality among agricultural workers: results from a death certificate-based case-control study - Patricia de Moraes Mello Boccolini; Carmen Ildes Rodrigues Froes Asmus; Juliana de Rezende Chrisman; Volney de Magalhães Câmara; Steven B. Markowitz; Armando Meyer (Instituto de Estudos em Saúde Coletiva da Universidade Federal do Rio de Janeiro, 2014)
INTRODUCTION: Pesticide consumption is very high in Brazil.OBJECTIVE: The present study investigated the stomach cancer mortality among Brazilian agricultural workers in Rio de Janeiro state.METHODS: In this case-control study, cases were individuals of both genders, aged ≥20 years, for whom cause of death was ascertained as stomach cancer. Controls were individuals with causes of death other than neoplasm and diseases of the digestive system. Crude and adjusted analyses were carried out. Stomach cancer mortality risk was then estimated for the agricultural workers according to the pesticide expenditures per municipality.RESULTS: Agricultural workers showed an elevated risk of stomach cancer mortality (adjusted OR=1.42; 95%CI: 1.33-1.78). This risk was higher among male workers, aged 50-69 years, white, and among workers with 1-7 years of education. Results also showed increasing stomach cancer mortality along with the increase of pesticide expenditure per agricultural worker.CONCLUSION: Stomach cancer risk among agricultural workers may be associated with pesticide exposure.